Retos de un programa socialista / [Julián Campo Sainz de Rozas, Julio Rodríguez López, Pedro Sabando Suárez] - Rodríguez López, JulioSabando, Pedro; Campo Sainz de Rozas, Julián
Tít. tomado de la cub.